Identification of Enzymes Homologous to Isocitrate Dehydrogenase That Are Involved in Coenzyme B and Leucine Biosynthesis in Methanoarchaea - Howell, David M. (American Society for Microbiology, 2000)
Two putative Methanococcus jannaschii isocitrate dehydrogenase genes, MJ1596 and MJ0720, were cloned and overexpressed in Escherichia coli, and their gene products were tested for the ability to catalyze the NAD- and NADP-dependent oxidative decarboxylation of dl-threo-3-isopropylmalic acid, threo-isocitrate, erythro-isocitrate, and homologs of threo-isocitrate. Neither enzyme was found to use any of the isomers of isocitrate as a substrate. The protein product of the MJ1596 gene, designated AksF, catalyzed the NAD-dependent decarboxylation of intermediates in the biosynthesis of 7-mercaptoheptanoic acid, a moiety of methanoarchaeal coenzyme B (7-mercaptoheptanylthreonine phosphate). These intermediates included (−)-threo-isohomocitrate [(−)-threo-1-hydroxy-1,2,4-butanetricarboxylic acid], (−)-threo-iso(homo)(2)citrate [(−)-threo-1-hydroxy-1,2,5-pentanetricarboxylic acid], and (−)-threo-iso(homo)(3)citrate [(−)-threo-1-hydroxy-1,2,6-hexanetricarboxylic acid]. The protein product of MJ0720 was found to be α-isopropylmalate dehydrogenase (LeuB) and was found to catalyze the NAD-dependent decarboxylation of one isomer of dl-threo-isopropylmalate to 2-ketoisocaproate; thus, it is involved in the biosynthesis of leucine. The AksF enzyme proved to be thermostable, losing only 10% of its enzymatic activity after heating at 100°C for 10 min, whereas the LeuB enzyme lost 50% of its enzymatic activity after heating at 80°C for 10 min.